2021
DOI: 10.5194/acp-21-15631-2021
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the spatiotemporal variations in ozone formation regimes across China from 2005 to 2019 based on polynomial simulation and causality analysis

Abstract: Abstract. Ozone formation regimes are closely related to the ratio of volatile organic compounds (VOCs) to NOx. Different ranges of HCHO/NO2 indicate three formation regimes, including VOC-limited, transitional, and NOx-limited regimes. Due to the unstable interactions between a diversity of precursors, the range of the transitional regime, which plays a key role in identifying ozone formation regimes, remains unclear. To overcome the uncertainties from single models and the lack of reference data, we employed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…We noted that the conclusion of this work was mainly derived from a case study for a specific episode in the urban area of Shenzhen, while previous studies demonstrated that the VOC- and NO x -limited regimes for O 3 production show temporal and spatial variation in the PRD and other urban agglomerations. Therefore, more efforts are needed to design a coordinated O 3 pollution control strategy. Recently, NO x emission reduction was found to be effective over the past decade, while VOC mitigation was less successful. , The reduction of NO x helps to reduce peak ozone levels, while the negative effect mainly happens at nighttime and in regions with less ozone pollution . Moreover, the continuous effort to control NO x emission not only shifts to the NO x -limited regime but also helps to reduce particulate pollution as particulate nitrate has become the major contributor to PM 2.5 . However, the nonlinearity between O 3 and particulate nitrate formation and primary emissions urges better understanding of their formation mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We noted that the conclusion of this work was mainly derived from a case study for a specific episode in the urban area of Shenzhen, while previous studies demonstrated that the VOC- and NO x -limited regimes for O 3 production show temporal and spatial variation in the PRD and other urban agglomerations. Therefore, more efforts are needed to design a coordinated O 3 pollution control strategy. Recently, NO x emission reduction was found to be effective over the past decade, while VOC mitigation was less successful. , The reduction of NO x helps to reduce peak ozone levels, while the negative effect mainly happens at nighttime and in regions with less ozone pollution . Moreover, the continuous effort to control NO x emission not only shifts to the NO x -limited regime but also helps to reduce particulate pollution as particulate nitrate has become the major contributor to PM 2.5 . However, the nonlinearity between O 3 and particulate nitrate formation and primary emissions urges better understanding of their formation mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, NO x emission reduction was found to be effective over the past decade, while VOC mitigation was less successful. 87,88 The reduction of NO x helps to reduce peak ozone levels, while the negative effect mainly happens at nighttime and in regions with less ozone pollution. 89 Moreover, the continuous effort to control NO x emission not only shifts to the NO x -limited regime but also helps to reduce particulate pollution as particulate nitrate has become the major contributor to PM 2.5 .…”
Section: Dependence Of O 3 Production On Pm 25 and Nitrogen Oxidesmentioning
confidence: 99%
“…In general, the urban areas were VOC‐limited owing to higher NO 2 emissions from traffic and industrial activities. Suburbs were NOx‐limited because of less anthropogenic activity and high BVOC emissions (X. Chen et al., 2019; R. Li et al., 2021). Under different SWPs, the O 3 ‐sensitive areas in the PRD urban area were substantially different.…”
Section: Resultsmentioning
confidence: 99%
“…Suburbs were NOx-limited because of less anthropogenic activity and high BVOC emissions (X. Chen et al, 2019;R. Li et al, 2021).…”
Section: Spatial Differences In O 3 Pollution Caused By Regional Tran...mentioning
confidence: 99%
“…Volatile organic compounds (VOCs) and nitrogen oxides (NO x ≡ NO + NO 2 ) are precursors of O 3 [ 27 ]. Many studies have explored the relationship, photochemical reaction mechanism, and influence factors between O 3 and its precursors [ 28 , 29 , 30 , 31 , 32 , 33 ]. Meteorological conditions are important factors of O 3 generation and transmission.…”
Section: Introductionmentioning
confidence: 99%